The Influence of Inflation and Stock Prices on Earnings Per Share of Bank Syariah Indonesia (BRIS) Stock - Nawwir Ar Rasyid Sulaiman; Muhammad Ikhsan Harahap; Imsar Imsar (Social Science Academic, 2026)
This study aims to analyze the effect of inflation and stock prices on Earnings Per Share at PT Bank Syariah Indonesia Tbk (BRIS) for the 2021-2025 period. This study employed a quantitative approach using secondary data analyzed using multiple linear regression. The results of partial hypothesis testing (t-test) indicate that inflation and stock prices do not significantly influence Earning Per Share. Consistent with this finding, simultaneous testing (F-test) also demonstrates that inflation and stock prices together have no significant effect on Earning Per Share. The coefficient of determination test results show a value of 44.1%. This indicates that inflation and stock prices explain fluctuations in Earning Per Share by 44.1%, while the remaining 55.9% is explained by factors outside the research model, such as the company's internal fundamental performance or other macroeconomic conditions. It can be concluded that, during this research period, external factors such as inflation and stock price movements were not the primary determinants of earnings per share at Bank Syariah Indonesia.